IMPROVING THE PERFORMANCE OF HOTELS ON THE BASIS OF THE USE OF THE FEATURES OF BUSINESS COMMUNICATIONS IN HOTEL COMPLEX - A. Kabanov (Вестник университета)
In the article reviewed and analyzed the role of verbal and nonverbal communication between guests and its employees, studied various psychological types of hotel guests and recommendations for maintenance every psycho.